Effect of borax-boric acid and ammonium polyphosphate on flame retardancy of natural fiber polyethylene composites - Kumar, Ritesh; Gunjal, Jayshree; Chauhan, Shakti (Maderas. Ciencia y Tecnología, 2022)
Wood fiber filled high density polyethylene composites (WPCs) were prepared using twin screw extruder and maleated polyethylene as a coupling agent. Bamboo fibers were initially treated with alkali (NaOH), boric acid - borax (Ba-Bx) and borax (Bx). The treated and untreated fibers were used in combination with ammonium polyphosphate (APP) to investigate their synergistic effects on thermal stability, flame retardancy and mechanical properties. Alkali pretreatment (5 % NaOH) of fibers showed significant improvement in performance of APP by increasing thermal stability in WPCs. The derivative thermogravimetric (DTG) results indicate significance of Ba-Bx in promoting char induction at lower temperatures (340 ºC) and thereby, improved the thermal stability in WPCs. Flammability decreased with addition of flame retardant additives. As compared to pure WPCs, composites containing APP 10 % / Ba-Bx 5 % exhibited maximum reduction in average heat release rate (HRR) by 69 %, peak heat release rate (PHRR) by 59 %, total heat released rate (THR) by 48 % and also increased time to ignition (TTI) by 62 %. However, no significant difference was found among the combinations i.e., APP with or without compounds towards reducing the flammability of WPCs. The strength properties also reduced significantly when boron compounds were added along with APP. In general, APP alone (15 %) is enough for imparting thermal stability and flame retardancy in WPCs.